Analisis Kinerja Sistem Informasi Manajemen Dalam Meningkatkan Efesiensi Operasional Perusahaan PT Pertamina Sekitar Pamulang - Ade Maulana; Churul Ain Yahya; Khairullah Tulfah; Rizky Imam Saputra; Veny Masullah; Samsoni; Apriani Handayani (Journal of Research and Publication Innovation, 2024)
Information systems are a means of transforming company data which is closely related to the company's efficiency in its operational activities. Along with technological developments, the application of information technology in companies is an important factor in increasing company value and competitiveness. So far there are still many companies that have not implemented information systems as expected because there are no standards for monitoring the use of information technology in companies. This research tries to find out how the information system is implemented at PT Pertamina. The sample was chosen because PT Pertamina is a State-Owned Enterprise with large assets. Data analysis uses qualitative analysis using a systematic review approach. The results of this research indicate that PT Pertamina has implemented an information system in the form of a management information system well in the company as a way to achieve company goals so as to achieve company efficiency and competitiveness.